Mitochondrial Replacement Therapy: In Whose Interests?. Issue 3 (2022) - Noohi, Forough; Ravitsky, Vardit; Knoppers, Bartha Maria; Joly, Yann
Abstract: Mitochondrial replacement therapy (MRT), also called nuclear genome transfer and mitochondrial donation, is a new technique that can be used to prevent the transmission of mitochondrial DNA diseases. Apart from the United Kingdom, the first country to approve MRT in 2015, Australia became the second country with a clear regulatory path for the clinical applications of this technique in 2021. The rapidly evolving clinical landscape of MRT makes the elaboration and evaluation of the responsible use of this technology a pressing matter. As jurisdictions with less strict or non-existent reproductive laws are continuing to use MRT in the clinical context, the need to address the underlying ethical issues surrounding MRT's clinical translation is fundamental.